A LINGUOSTYLISTIC INTERPRETATION OF THE LEXEME “HEART” IN THE LATER CHAPTERS OF JANE AUSTEN’S “PRIDE AND PREJUDICE” - Ruzikulov Fazliddin Shukurovich; Musoyeva Khayitgul Urokovna (Scholar Express Journal, 2026)
This study continues the linguostylistic investigation of the lexeme heart in Jane Austen’s Pride and Prejudice, focusing on twelve excerpts from the latter part of the novel. The research examines how heart functions as a linguistic and stylistic marker of emotional maturity, moral awareness, and reconciliation. Using semantic, pragmatic, and contextual stylistic analysis, the study reveals that in the final chapters, Austen employs heart to express moral self-reflection, empathy, and resolution rather than romantic excitement. The findings suggest that Austen’s later usage of heart evolves from expressions of passion to representations of moral integrity and human connection, reflecting the author’s broader ethical vision of emotion harmonized with reason
Keywords: linguostylistics; semantics; pragmatics